PLAK VE PÜSTÜLER PSORİASİSDE ASPROSİN MOLEKÜLÜNÜN İMMÜNREAKTİVİTESİNİN İMMÜNOHİSTOKİMYASAL OLARAK İNCELENMESİ - BALCI, HATİCE KÜBRA KARATAŞ (Fırat Üniveristesi, 2025)
Çalışmamızda plak psoriasis ve püstüler psoriasis tanısı konulan hastaların doku örneklerinde asprosin immünreaktivitesinin immünohistokimyasal olarak incelenmesi amaçlandı. Çalışmada 20 adet plak psoriasis ve 20 adet püstüler psoriasis tanısı konmuş 40 adet deri örneği ve kontrol grubunu oluşturacak 20 adet hastalıklı doku komşuluğundaki herhangi bir patolojiye rastlanmayan sağlıklı deri örneği olmak üzere toplam 60 adet deri örneği kullanıldı. Diğer dermatolojik hastalıklar veya malignite tanısı konmuş ve diabetes mellitusu olan hastaların deri örnekleri çalışmadan dışlandı. Elde edilen deri örneklerinin tanıları doğrulandıktan sonra parafin bloklardan 5-6 µm kalınlığında alınan doku kesitlerine asprosin için indirekt immünohistokimyasal boyama yapıldı. Bu yöntemle primer antikorla nemli ortamda inkübe edilmiş dokulara biyotinli sekonder antikor uygulanacak ve streptavidinli enzimle (peroksidaz veya alkalen fosfataz) inkübasyon yapıldı ve enzim substratı olan 3-Amino-9-Ethylcarbazole (AEC) veya 3, 3'-diaminobenzidine (DAB) kromojenleri uygulandı. Boyamada immünreaktivitenin yaygınlığı (0.1: <%25, 0.4: %26-50, 0.6: %51-75, 0.9: %76-100) ve şiddeti (0: yok, +0.5: çok az, +1: az, +2: orta, +3: şiddetli) kriter alınarak bir histoskor oluşturuldu. Hesaplamalarda histoskor = yaygınlık x şiddet formülü kullanıldı. Elde edilen veriler statistical package for the social sciences (SPSS, version 22.0) (Chicago, IL, USA) paket programı kullanılarak analiz edildi. Kolmogorov-Smirnov ve Shapiro-Wilk normallik testleri yapıldıktan sonra iki gruplu değişkenlerde bağımsız örneklem t testi iki gruptan fazla değişkenlerde ise varyans analizi (ANOVA) kullanıldı. p<0.05 değeri istatistiksel olarak anlamlı kabul edildi. Bu çalışmada asprosin histoskorlarının ortalaması kontrol grubunda 0.530±0.146, plak psoriasisli hasta grubunda 0.570±0.146, püstüler psoriasisli hasta grubunda ise 1.605±0.392 olarak tespit edildi. Asprosin immünreaktivitesinin immünohistokimyasal incelenmesinde kontrol grubu ile plak psoriasisli hasta grubunda istatistiksel olarak anlamlı bir farklılık tespit edilemedi (p>0.874). Püstüler psoriasisli hasta grubunda ise hem kontrol hem de plak psoriasisli hasta gruplarına göre istatistiksel olarak anlamlı bir artış tespit edildi (p<0.001, p<0.001, sırasıyla). Bu çalışmada püstüler psoriasisli hasta grubundaki histoskorların hem kontrol hem de plak psoriasili hasta grubuna göre belirgin artmış olması püstüler psoriasisin IL-1 ve IL-36 gibi otoinflamatuar yolakların baskın olduğu yoğun nötrofilik bir inflamasyonla seyretmesi ile ilişkilendirildi. Bu bulgu asprosinin şiddetli inflamasyona yanıt olarak yükseldiğini ve püstüler psoriasiste inflamasyonun şiddetini ortaya koyan potansiyel bir biyobelirteç olabileceğini düşündürmektedir. İleride yapılacak çalışmalarla bu konuda daha net veriler elde edilebilir. Anahtar Kelimeler: Psoriasis, püstüler psoriasis, asprosin

In this study, a total of 60 skin samples were used, including 20 from patients diagnosed with plaque psoriasis, 20 from patients diagnosed with pustular psoriasis, and 20 healthy skin samples obtained from areas adjacent to diseased tissue without any pathological findings, serving as the control group. Skin samples from patients diagnosed with other dermatological diseases, malignancies, or diabetes mellitus were excluded from the study. Following the confirmation of diagnoses, tissue sections of 5–6 µm thickness were obtained from paraffin-embedded blocks, and indirect immünohistochemical staining for asprosin was performed. In this method, the tissues were incubated with the primary antibody in a humid environment, followed by the application of a biotinylated secondary antibody and incubation with a streptavidin-conjugated enzyme (peroxidase or alkaline phosphatase). Subsequently, chromogens such as 3-Amino-9-Ethylcarbazole (AEC) or 3,3?-Diaminobenzidine (DAB) were applied as enzyme substrates. A histoscore was calculated based on the extent of immünoreactivity (0.1: <25%, 0.4: 26–50%, 0.6: 51–75%, 0.9: 76–100%) and staining intensity (0: none, +0.5: very weak, +1: weak, +2: moderate, +3: strong). The formula histoscore = extent × intensity was used for these calculations. The obtained data were analyzed using the Statistical Package for the Social Sciences (SPSS, version 22.0) (Chicago, IL, USA). After performing the Kolmogorov-Smirnov and Shapiro-Wilk normality tests, independent samples t-test was used for comparisons between two groups, and analysis of variance (ANOVA) was used for comparisons involving more than two groups. A p-value of <0.05 was considered statistically significant. In this study, the mean asprosin histoscore of the control group was found to be 0.530 ± 0.146, whereas the mean histoscore of the psoriasis patient group was 0.570 ± 0.146. The mean asprosin histoscore of the pustular psoriasis group was 1.605 ± 0.392. İmmünohistochemical analysis of asprosin immünoreactivity revealed no statistically significant difference between the plaque psoriasis group and the control group (p = 0.874). However, a statistically significant increase in asprosin immünoreactivity was observed in the pustular psoriasis group compared to the control group (p < 0.001). Additionally, when compared to the plaque psoriasis group, the pustular psoriasis group showed a statistically significant increase in asprosin immünoreactivity (p < 0.001). The aim of this study was to evaluate the immünohistochemical expression of the asprosin molecule in healthy skin and in two subtypes of psoriasis: plaque and pustular psoriasis. While asprosin immünoreactivity was significantly increased in pustular psoriasis, it remained at levels comparable to healthy skin in plaque psoriasis. This difference suggests that the elevated levels of asprosin in pustular psoriasis may be associated with the intense neutrophilic inflammation characteristic of this subtype, which is dominated by autoinflammatory pathways such as IL-1 and IL-36. In conclusion, asprosin may be considered a potential biomarker reflecting the severity of inflammation, particularly in pustular psoriasis. Further studies are needed to clarify its role and diagnostic value. Key words: Psoriasis, pustular psoriasis, asprosin
This study aimed to investigate the immunoreactivity of asprosin in tissue samples of patients diagnosed with plaque psoriasis and pustular psoriasis by means of immunohistochemical analysis
Keywords: Dermatoloji